Direct and indirect impacts of liberal immigration policies on the inflow of multinationals in the U.S. - Geiguen Shin (Kiel Institute for the World Economy (IfW), 2019)
Many studies suggest that stringent labor protection and higher labor costs in host countries can limit foreign direct investment. This implies that foreign firms are sensitive to the flexibility of the labor market in the U.S. The U.S. has experienced increasing immigrants, which have preserved the stable labor supply in the U.S. market. The U.S. is a good case to test the relationship between immigration and FDI because the U.S. is not only the largest host and home country of FDI but also the country that has one of the highest immigrant populations and experiences a significant reduction in labor supply and an increase in the minimum cost of labor. Utilizing a time-series analysis from 1970 to 2016, this study suggests that the expansive immigration policies directly increase FDI inflows in the U.S., and indirectly increase FDI inflows throughout lowering potential labor costs and securing a stable labor supply.
http://dx.doi.org/10.7910/DVN/0V82MQ
Keywords: F16; J15; 330; foreign direct investment; immigration policy; labor cost